Systemic view of the market opportunities for fresh cuts convenience in Ghana. (2016) - Banson, Kwamina Ewur; Sun, Daowei; Banson, Irene Baaba
The demand for convenience fruits offers opportunities for farmers, vendors and processors. Currently, processing facilities in Ghana are plagued with expensive supply of raw materials and interrupted electricity supply. As a result, retailers have taken over the fresh-convenience fruit market. This paper report on the status of fresh fruit convenience markets among vendors and hawkers, and identify the challenges that they face. A market survey conducted showed that, vendors are able to generate between 45-90 Ghana Cedis as revenue from fruits sales per-day. However, vendors stock becomes more expensive as a result of fruit perishing, but they have difficulty passing on increased costs to consumers. This study revealed that 65.9% of total fruit production is wasted between farm gate and retail end. The results of this paper will help governments to improve the high ethical standards and reduce business and legal risk associated with industrial vending fruit chains.